Adsorption, Bioavailability, and Toxicity of Cadmium to Soil Microorganisms - Choi, Jaeyoung (TAYLOR & FRANCIS INC, 2009)
The influence of adsorption on cadmium toxicity to soil microorganisms in soils was quantified as a function of solution and sorbent characteristics. The influence of adsorption on cadmium toxicity to soil microorganisms was assessed indirectly through the relative change in microbial hydrolysis of fluorescein diacetate (FDA) as a function of total Cd concentration and sorbent characteristics. The sequence of relative percentage of FDA hydrolysis was reference smectite (RS) untreated Vertisol (UV) dithionate-citrate-bicarbonate (DCB)-treated Vertisol (DV) H2O2-treated Vertisol (HV) in suspensions containing the same total Cd concentrations. The correlation between the percentage of FDA hydrolysis and activity of Cd2+(aq) illustrates that RS has a higher capacity of Cd adsorption. The microbial activity of RS was higher and the toxicity was lower than that of other soil samples. The HV had lower capacity of Cd adsorption so that its FDA hydrolysis was low and the Cd toxicity was high.
Keywords: HEAVY-METAL RESISTANCE; SORPTION; IONS